THU0286 Extra- and Intracranial Cerebral Vasculitis in Giant Cell Arteritis: an Observational Study. (9th June 2015) - Larivier, D.; Sacre, K.; Klein, I.; Hyafil, F.; Choudat, L.; Chauveheid, M.-P.; Papo, T.
Abstract : Background: Giant cell arteritis (GCA) is the most frequent vasculitis in patients aged over 50 years old in Europe and North America. Stroke may occur in patients with GCA. In most cases, stroke is related to vasculitis of extracranial cerebral arteries causing vertebral or internal carotid arteries stenosis. However cerebrovascular accidents are rare in the setting of GCA and specific involvement of cranial arteries may be difficult to distinguish from non-specific atherosclerotic lesions in the elderly Objectives: The aim of our study was to highlight the clinical spectrum and long-term follow-up of GCA-specific stroke. Methods: Medical charts of all patients followed in a French department of internal medicine for GCA between January 2008 and January 2014 were retrospectively reviewed. Patients with cerebrovascular accidents at GCA diagnosis were included. Diagnosis of GCA was based on American College of Rheumatology criteria. Transient ischemic attacks and stroke resulting from an atherosclerotic or cardioembolic mechanism were excluded. Clinical features, GCA-diagnosis workup, brain imaging, cerebrospinal fluid (CSF) study, treatment, and follow-up data were analysed. Results: From January 2008 to January 2014, 97 patients have been followed for GCA. Among them, 8 biopsy-proven GCA patients (mean age 70±7.8 years, M/F Sex ratio 3/1) had stroke at GCA diagnosis. Six patients reported headache and visual impairment. Brain MR angiography showed involvement of vertebral and/or basilar arteries in all cases with multiple or unique ischemic lesions in the infratentorial region of the brain in all but one case. Intracranial cerebral arteries involvement was observed in 4 cases including 2 cases with cerebral angiitis. Long lasting lesions on diffusion-weight brain MRI sequences were observed in 1 case. All patients received steroids for a mean of 28.1±12.8 months. Side effects associated with long-term steroid therapy occurred in six patients. Relapses occurred in 4 patients and required immunosuppressive drugs in 3 cases. After a mean follow-up duration of 36.4±16.4 months, all but one patient achieved complete remission without major sequelae. Conclusions: The conjunction of headache with vertebral and basilar arteries involvement in elderly is highly suggestive of stroke associated with GCA. Intracranial cerebral arteries involvement with cerebral angiitis associated with long lasting brain lesions on diffusion-weight brain MRI sequences may occur in GCA. Both frequent relapses and steroid-induced side effects argue for the use of immunosuppressive agents combined with steroids as first-line therapy. Disclosure of Interest: None declared